Gene expression patterns of immune markers in rainbow trout during the early stages of seawater infections with Piscirickettsia salmonis - Levipan, Héctor A.; Wicki, Hernán; Barrios-Henríquez, Fernanda; Pozo-Solar, Francisco; Irgang, Rute; Avendaño-Herrera, Ruben (Frontiers in Veterinary Science, 2025)
Piscirickettsiosis is a fish disease caused by the facultative intracellular bacterium Piscirickettsia salmonis. This research aimed to study the immune response of rainbow trout (Oncorhynchus mykiss) during the first seawater farming stage upon infection with P. salmonis. Fish were challenged by immersion with P. salmonis type strain LF-89T (genogroup 1) and the field isolates Psal-103 (LF-89-like genotype or genogroup 3) and Psal-104 (EM-90-like genotype or genogroup 4). A group of fish was treated with sterile AUSTRAL-SRS (Salmon Rickettsial Septicemia) medium. This group and fish from the infectious treatment and negative control were kept in a pilot-scale recirculating aquaculture system (RAS) for monitoring purposes. The P. salmonis load in trout skin and seawater was measured by reverse transcription-quantitative PCR (RT-qPCR) targeting an internal transcribed spacer (ITS) region. ITS transcripts were undetectable in trout skin samples before challenges and in trout skin from the sterile SRS medium treatment after challenges. The number of ITS transcripts in RAS seawater samples was 2.21 × 104 ± 8.99 × 103 copies per ng of total RNA at 15 days post-infection (dpi) and undetectable at 30 dpi. ITS transcript levels in trout skin were at maximum 15 dpi for all P. salmonis. For instance, the load of ITS transcripts in the skin of Psal-103-infected trout was 5.44 ± 2.58 × 106 copies per ng of total RNA at 15 dpi. There were no significant differences in mortality between infection treatments. The cumulative mortality of trout from the negative control group was significantly lower than those from P. salmonis-infected trout. The expression of nine immunity-related genes was determined by RT-qPCR in the gills, spleen, liver, muscle, and head kidney tissues. An innate inflammatory response was associated with the expression of the saa and tnf-α genes in surviving fish. In addition, the downregulation of oncmyk-dbb and IGHM genes indicates that P. salmonis can interfere with the activation of CD4+ T cells and impair humoral immunity. Our findings suggest that the isolate Psal-104 has a higher immunogenic potential. Finally, our results support the use of non-lethal and non-invasive methods for analyzing fish skin as an early surveillance tool for piscirickettsiosis.